EXPLORING THE HUMAN CAPITAL DYNAMICS OF BANDUNG'S DIGITAL CREATIVE INDUSTRY ECOSYSTEM - Nabiela Rizki Alifa (Jurnal Al-Iqtishad, 2024)
Digital creative industry holds immense potential to drive economic growth, particularly in Bandung, known for its dynamic creative environment. Realizing this potential requires a deep understanding of the human capital as the primary resource in developing this industry. This study examines its dynamics based on the theories of creative class, human capital, knowledge management, and effectuation. Through a qualitative approach, the research utilizes in-depth interviews with various stakeholders, including creative professionals, academics, and government representatives, to gain insights into the opportunities and challenges faced by human capital in this industry. Data analysis techniques include Latent Dirichlet Allocation topic modeling, word frequency analysis, and word co-occurrence network analysis. The findings suggest that Bandung has potential to develop a strong digital creative industry, demonstrated by the presence of talented workforce, high entrepreneurial spirit, and a supportive community. However, several challenges need to be addressed, such as skills gaps, limited access to funding, and the need for stronger policy support. Moreover, synergistic collaboration among stakeholders is crucial to create an ecosystem that supports human capital development and fosters the sustainable growth of Bandung's digital creative industry. These efforts include enhancing knowledge-sharing, promoting innovation, and implementing policies that can attract and retain creative talents.